2016
DOI: 10.1038/ncomms13646
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the magnetic coupling and anisotropy at the molecule–magnetic surface interface in molecular spintronic devices

Abstract: A challenge in molecular spintronics is to control the magnetic coupling between magnetic molecules and magnetic electrodes to build efficient devices. Here we show that the nature of the magnetic ion of anchored metal complexes highly impacts the exchange coupling of the molecules with magnetic substrates. Surface anchoring alters the magnetic anisotropy of the cobalt(II)-containing complex (Co(Pyipa)2), and results in blocking of its magnetization due to the presence of a magnetic hysteresis loop. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 53 publications
3
46
0
Order By: Relevance
“…Such changes are generally ignored in organic electronics, where the conductive electrode basically represents an infinite reservoir of electrical carriers. Spin transport, in contrast, may be significantly influenced by the spin polarization of the boundary, hybridized, atomic layer of the magnetic material 65 . Hybridization effects able to modify inorganic ferromagnetic materials were reported in 2013 for the Co/zinc methyl phenalenyl ZMP interface 54 (Fig.…”
Section: The Inorganic Sidementioning
confidence: 99%
“…Such changes are generally ignored in organic electronics, where the conductive electrode basically represents an infinite reservoir of electrical carriers. Spin transport, in contrast, may be significantly influenced by the spin polarization of the boundary, hybridized, atomic layer of the magnetic material 65 . Hybridization effects able to modify inorganic ferromagnetic materials were reported in 2013 for the Co/zinc methyl phenalenyl ZMP interface 54 (Fig.…”
Section: The Inorganic Sidementioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] Recently it has been reported that phosphonate complexes can be condensed to surfaces to engineer magnetic exchange and anisotropy towards molecular spintronic devices. 21 Many efforts have also been made to understand the magneto structural behaviour of phosphonate-derived materials, with the studies by Zheng, Bellitto and Clearfield being important contributions. [9][10][11]20,22 However fewer studies have been done for phosphate based materials.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 6d, a ferrimagnetic substrate was first composed by a single substitution of the Vs. When a ferromagnetic SMM was formed on this substrate, it antiferromagnetically interacted with the host, leading the whole system to become AFM [100]. positioned on the edge of the LTMDs [96].…”
Section: Analysis From Electronic Structuresmentioning
confidence: 99%